Unrest and Violence: 2019 - Du Plessis, Willemien; Pienaar, Juanita; Koraan, René; Stoffels, Myrone (Journal of Law, Society and Development, 2021)
The year 2019 was characterised by gang and taxi violence. In the reporting period, the South African Police Services published the 2018 crime statistics, revealing an alarming increase in violent crimes. The annual report of the Inspectorate Judge of Correctional Services revealed that prisons remain overcrowded. Section 12(1)(a) of the Gatherings Act 205 of 1993 was declared unconstitutional. Regulations to assist dependents of victims of apartheid in relation to basic and higher education, were amended. Police corruption was addressed and neighbourhood watches in the Western Cape were accredited. In this article, two cases that dealt with parole are discussed regarding the calculation of the date of parole, as well as a court’s order regarding the minimum sentence that a prisoner has to serve, before he or she can apply for parole. A decision of the Western Cape High Court is discussed in relation to the treatment of transgender prisoners. The independence of the Judicial Inspectorate of Correctional Services in relation to the Sonke case is dealt with. A Bill introduced a new military court structure, as well as described the role of the military police. A private member Draft General Intelligence Law Amendment Bill, 2019, now provides for more oversight of the intelligence services regarding finances. The note also refers to the destruction of firearms, the issuing of licences for firearms with new components, as well as the court’s decision in Corruption Watch v Arms Procurement, where the court overturned the Commission of Inquiry’s report regarding controversial arms procurement of 1997–1999. Gender-based violence has still not been addressed adequately, despite promises to strengthen legislation in this regard. In relation to terrorism, new financial regulations are being put in place.